1982
DOI: 10.1126/science.7089553
|View full text |Cite|
|
Sign up to set email alerts
|

Hair-Cell Innervation by Spiral Ganglion Cells in Adult Cats

Abstract: A horseradish peroxidase technique was used to trace the peripheral terminations of two types of ganglion cells in adult cats. It was found that large, usually bipolar ganglion cells end on inner hair cells and small, usually pseudomonopolar ganglion cells end on outer hair cells. Thus, a virtually complete segregation of afferent neural inputs from the two types of hair cells was directly confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
127
1
6

Year Published

1996
1996
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 278 publications
(135 citation statements)
references
References 8 publications
1
127
1
6
Order By: Relevance
“…Large type I neurons with peripheral processes synapsing on inner hair cells represent approximately 90Y95% of the afferent auditory neurons and are myelinated. The remaining small type II neurons innervate the outer hair cells and are unmyelinated (Spoendlin 1969;Kiang et al 1982Kiang et al , 1984 (Berglund and Ryugo 1986;Hafidi 1998). Our previous study demonstrated that a small number of neurons with small nuclei survive after acute ouabain treatment (Schmiedt et al 2002).…”
Section: Introductionmentioning
confidence: 88%
“…Large type I neurons with peripheral processes synapsing on inner hair cells represent approximately 90Y95% of the afferent auditory neurons and are myelinated. The remaining small type II neurons innervate the outer hair cells and are unmyelinated (Spoendlin 1969;Kiang et al 1982Kiang et al , 1984 (Berglund and Ryugo 1986;Hafidi 1998). Our previous study demonstrated that a small number of neurons with small nuclei survive after acute ouabain treatment (Schmiedt et al 2002).…”
Section: Introductionmentioning
confidence: 88%
“…In cats, each inner hair cell is innervated by a single synapse from ten to 20 type I SG neurons (Kiang et al 1982;Liberman et al 1990;Spoendlin 1969Spoendlin , 1975Spoendlin , 1981. Type I cells comprise roughly 95 % of the SG population; they provide the main information pathway to the central auditory system (Kiang et al 1982) and therefore represent the neural substrate for cochlear implant (CI) function. In sensorineural hearing loss, the hair cells degenerate, the distal dendrites of the SG neurons (radial nerve fibers) begin to retract, and subsequently the ganglion cell somata in the cochlear modiolus also degenerate.…”
Section: Introductionmentioning
confidence: 99%
“…The neurons that give rise to these fibers have been subdivided into two types depending on which receptor cell population is contacted in the cochlea. Type I neurons provide the afferent innervation of inner hair cells, whereas type II neurons provide the afferent innervation of outer hair cells (Spoendlin 1971;Kiang et al 1982). It is clear that type I neurons, which comprise more than 90% of all primary auditory neurons, provide the main pathway for auditory input to the brain.…”
Section: Introductionmentioning
confidence: 99%